E-SAFETY PROBLEMS AND PROTECTION METHODS - Inķēna, Kristiāna; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
E-security is the protection of all data stored on computer networks and computer systems against damage, loss or unauthorized access. E-security, based on the definition, is all that can be related to the safe use of the Internet, personal knowledge and behavior, and ethics on the Internet. There are examined following threats to websites - the leakage of information, cross-site scripting attacks, injection, unsafe direct object reference, CSRF, security configuration errors, unsafe cryptographic repository, and redirection and transmission without validation. The author reviews the cyber attacks recorded in Latvia during this year, as well as statistics on recorded incidents during the last year. The final chapter of the work provides a table that summarizes methods and tools for protecting websites from attacks.